Evaluate the Program in Strengthening Group Business’s Capital Effectiveness of Beef Cattle Farm to Increasing Farmers Income in Kupang Regency - J. T. V. Hanin; M. Krova; U. Lole (Universitas Bengkulu, 2022)
Research has been conducted, and this study aims to know the effectiveness and income of the program in Strengthening Group Business’s Capital (SGBC) by performance, the assistance of government institutions, and local institutions, then point to income. The data collecting method used multi random sampling such-stage as the first seven district samples are selected based on purposive random sampling, and the second 200 respondents are chosen. Data, then, are analyzed by applying analysis of descriptive and inferential use of SPSS and SMART PLS software. The result shows that performance, assistance, and local institutions significantly affect program effectiveness by direct effect and income by indirect effect with the role of mediating factors, While point significantly affects farmers' income.